Intermediate Microeconomics : A modern approach - Varian Hal R. (New York : W. W. Norton and Company, 1996)
This Norton International Student Edition has been produced solely for use outside the united states and Canada. It is an unabridged version of the original hardcover edition.
includes index
aau, 8/08/2022
Loan